Studi Penggunaan Mannan oligosaccharide (MOS) terhadap kelulushidupan dan Pertumbuhan Artemia - Indariyah, Indariyah; SPJ, Nur Taufiq; Ismunarti, Dwi Haryo (Departemen Ilmu Kelautan, Fakultas PerikanJurusan Ilmu Kelautan, Universitas Diponegoro)
Artemia is the most enthused nature feed in the fish and crustaceans hatchery operations, which causing the increase of Artemia’s demand and the prices. Hence, we need to develop the Artemia production through aquaculture. The first larvae development are the crucial time which causes a big risk of death and the feed compositions still contain many harmful bacteria that can reduce the production of Artemia. By giving MOS for Artemia, can be expected to reduce mortality rates and accelerate the growth. The purpose of this research is to investigate the percentage of using MOS against the survival rate and growth of Artemia. The additional feeding treatments were 0% (A), 1% (B), 3% (C), and 5% (D) of MOS added to the amount of phytoplankton. ANOVA is used for analysing the data, then continued with Polinomial Ortogonal test. The Results showed that different treatment significantly different to the survival rate and growth of Artemia. The best survival rate (39,50%) was from the C treatment, indicated by the high weight (753,37 μg), and longest growth length (9,0 mm). Water quality during the research is still in a decent range for the life of Artemia. This research can be concluded thah the best percentage of MOS given for bast survival rate growth by weight and length were 4,1%, 3,7% and 3,6% respectively.